ACCURACY OF DIFFUSION-WEIGHTED MRI (DW-MRI) IN PROSTATE CANCER DETECTION TAKING HISTOPATHOLOGY AS GOLD STANDARD (The Research of Medical Science Review, 2024)
Objective: To evaluate how accurately diffusion weighted MRI (DW-MRI) can identify malignant prostate lesions, using histopathology as the definitive standard for diagnosis.Methods: This cross-sectional validation study including 148 patients suspected of prostate cancer was conducted in radiology unit of Sindh Institute of Urology and Transplantation from July-2024 to September-2024. In all patients DW-MRI was performed and the DW-MRI findings were correlated with histopathology findings to determine the diagnostic accuracy of DW-MRI. Results: Mean age was 51.3±10.6 years. Out of 148, 107 (72.2%) presented with hematuria, and 125 (84.4%) presented with urinary retention. Regarding diagnostic accuracy, DW-MRI was 88.1% specific, 85.1% sensitive, with 76.9% PPV and 92.7% NPV. The overall diagnostic accuracy was 87.2%.Conclusion: DW-MRI carries a good sensitivity and specificity for diagnosis of malignant prostate lesions. Therefore, it can be used to assess early meta-static spread in prostate cancer patients and help us to better decide the treatment goals.